The Urgency of Social Studies Education in a Multicultural Society - Zainuddin, Zurahmah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
Multicultural society is a society that is synonymous with diversity. In Indonesia, diversity is a necessity which in the end does not only bring positive influences, but also negative influences attached to it. Because of the existing diversity, it does not only make Indonesia a unique country but at the same time creates frictions that can lead to the breakdown of unity which is the lofty ideal of the nation's founding fathers. Through IPS education, it is hoped that future generations will be able to survive amidst of increasingly complex frictions of a multicultural society. Instilling human values in diversity is the main goal of the expected learning process. This study uses the method of literature study. The data were obtained through various literature, both from books and journals related to the topics discussed and presented descriptively. Data obtained from various literatures were analyzed qualitatively. Therefore, the actualization of social studies education is a preventive step that can provide students with future generations in dealing with all problems of a multicultural society which in the end becomes an important thing in creating peace in a multicultural country.